The Changing Perception of Threats to the Nation-State and the Changing Structure of Military Organization in Türkiye from the Republic to the Present Day - Atilla Öztekin; Temmuz Gönç Şavran (İstanbul Üniversitesi Sosyoloji Dergisi)
This study aims to describe and assess the evolution of perceived threats to the nation-state and the structural changes within military institutions across three distinct periods in the history of the Turkish Republic. This analysis is conducted through a literature review framed within the context of the discussions on military sociology. Military organizations change according to the types of perceived threats, with the forms of collective threats with which the state is directly or indirectly involved transform. The types of threats had been mass coordinated destruction during the War of Independence and today has turned into subnational threats in the pattern of a flexible network of violence. Türkiye’s military institution is historically based on compulsory military service under a central state authority and continues to undergo a process of increased flexibility and professionalization within its organizational framework. Consequently, the Turkish Armed Forces can be characterized as a semi-professional military organization. Its emphasis on regional defense and institutional professionalization initiatives have led to an increase in the number of professional soldiers within its ranks, surpassing the number of individuals who fulfill compulsory service obligations.